Analisis Determinan Volume Ekspor Karet Alam Indonesia - Putri Cohara, Shallomitta Angelina; Marhaeni, Anak Agung Istri Ngurah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Natural rubber is one of the non-oil and non-gas export commodities or plantation crops that plays a crucial role in Indonesia's economy and can also enhance Indonesia's reputation in international trade. This commodity significantly contributes to the country's foreign exchange reserves. Indonesia is one of the largest rubber producers. The objectives of this research are 1) To analyze the simultaneous and partial effects of Indonesia's natural rubber production, international natural rubber prices, and the US Dollar exchange rate on Indonesia's natural rubber export volume from 1991 to 2022. 2) To analyze the sequence of the impact of variables, including the amount of Indonesia's natural rubber production, international natural rubber prices, and the US Dollar exchange rate on Indonesia's natural rubber export volume from 1991 to 2022. The data used are secondary data with observations from 1991 to 2022. To achieve the research objectives, descriptive statistical analysis and multiple linear regression analysis are employed. Based on the analysis results, it is found that 1) Simultaneously, Indonesia's natural rubber production, international natural rubber prices, and the US Dollar exchange rate have a significant influence on Indonesia's natural rubber export volume from 1991 to 2022; 2) Partially, Indonesia's natural rubber production has a significant positive impact on the export volume of Indonesian natural rubber. International natural rubber prices and the US Dollar exchange rate have positive but not significant effects on Indonesia's natural rubber export volume; 3) The sequence of the influential variables on Indonesia's natural rubber export volume is the amount of Indonesia's natural rubber production, international natural rubber prices, and the US Dollar exchange rate. The empirical implications of these findings are that changes in international prices and the US Dollar exchange rate do not directly affect Indonesia's natural rubber export volume. Other factors such as Indonesia's natural rubber production have a more significant influence on the export volume.